FAKTOR-FAKTOR PENENTU PARTISIPASI DALAM PROGRAM PROLANIS: STUDI KASUS DI PUSKESMAS KOTA CILEGON - Mardiyah Mardiyah; Muhammad Subuh (Jurnal Kebijakan Pembangunan Daerah, 2024)
The Controlled Prolanis Participant Ratio (RPPT) in Health Centers throughout Cilegon City in 2023 only reached 0.68%, far below the target. The ratio indicates participants' low utilization of Prolanis services. This study used an analytical observational method with a cross-sectional approach aimed at analyzing factors that influence the utilization of Prolanis in Cilegon City in 2024 with a cross-sectional design. The sample consisted of 90 Prolanis participants, and the data were analyzed using logistic regression. The results showed a Prolanis utilization rate of 61.1%. Chi-square analysis showed a significant relationship (p < 0.05) between Prolanis utilization and gender (p = 0.034), education (p = 0.009), knowledge (p = 0.006), family support (p = 0.000), and the role of officers (p = 0.000). However, no significant relationship was found with age (p = 0.729) and occupation (p = 1.000). Logistic regression analysis identified family support as the most influential factor, with a value of β = 3.98, p = 0.000, and OR = 53.5. These results emphasize the importance of increasing Communication, Information, and Education (KIE) efforts to instill awareness of the importance of regular participation in Prolanis activities. In addition, the formation of groups or associations of Prolanis participants and families in every Health Center throughout Cilegon City is recommended to support the success of this program.